A recent study of natural hydrogels: improving mechanical properties for biomedical applications - Shukla, Atharva; Syaifie, Putri Hawa; Rochman, Nurul Taufiqu; Jaya Syaifullah, Syahnanda; Jauhar, Muhammad Miftah; Mardliyati, Etik (Biomedical materials (Bristol), 2025)
Natural polymer-based hydrogels, generally composed of hydrophilic polymers capable of absorbing large amounts of water, have garnered attention for biomedical applications because of their biocompatibility, biodegradability, and eco-friendliness. Natural polymer-based hydrogels derived from alginate, starch, cellulose, and chitosan are particularly valuable in fields such as drug delivery, wound dressing, and tissue engineering. However, compared with synthetic hydrogels, their poor mechanical properties limit their use in load-bearing applications. This review explores recent advancements in the enhancement of the mechanical strength of natural hydrogels while maintaining their biocompatibility for biomedical applications. Strategies such as chemical modification, blending with stronger materials, and optimized cross-linking are discussed. By improving their mechanical resilience, natural hydrogels can become more suitable for demanding biomedical applications, like tissue scaffolding and cartilage repair. Additionally, this review identifies the ongoing challenges and future directions for maximizing the potential of natural polymer-based hydrogels in advanced medical therapies.